Methicillin-Resistant Staphylococcus aureus (MRSA) Detection from the Hands of Jatinangor Community Health Center’s Health Care Providers - Jeevanisha Patmanathan; Sunarjati Sudigdoadi; Ricky Adriansjah (Althea Medical Journal, 2015)
Background: Methicillin-resistant Staphylococcus aureus is a bacterium that is resistance towards β-lactam antibiotics, and it seems to be one of the leading causes of nosocomial infections. Hands of the health care workers are said to be the main source for the nosocomial transmission. Thus, the study aims to determine methicillin-resistant S. aureus from the hands of Jatinangor Community Health Center’s health care workers.Methods: Samples were taken from the hands of 30 Jatinangor Community Health Center’s staffs, including medical and paramedical; from October 2012 to November 2012. Then, these samples underwent further laboratory examinations, starting from culture, identification and susceptibility test towards cefoxitin, in identifying methicillin-resistant S. aureus.Results: Out of the 30 samples taken, 6 samples (20%) were positive for S. aureus isolates. In which, 4 (13.33%) of the samples were positive for methicillin-resistant S. aureus.Conclusions: Since, health care workers are the main people in contact with patients and maintaining proper hand hygiene makes a huge difference; hand hygiene should be given adequate attention for the benefit of all. [AMJ.2015;2(1):217–20]